Resolution of the Youth Scientific Conference (with international participants) "Wildlife systems and economy of the borderline territories of Tuva and Mongolia: fundamental problems and prospects of sustainable usage” - ., . . (The New Research of Tuva, 2012)
Resolution of the Youth Scientific Conference (with international participants) "Wildlife systems and economy of the borderline territories of Tuva and Mongolia: fundamental problems and prospects of sustainable usage”